Study on: Multicast Routing Protocols: MOSPF and DVMRP - I. Ali, Rasan; A. Shaban, Awaz (Qubahan Academic Journal, 2023)
Today’s networks are designed to reliably transmit traffic such as data from point to point i.e. unicasting, or from point to multipoint i.e. broadcasting. Multimedia places further demands on the network. First of all, multimedia traffic, such as audio or video, cannot tolerate delays in delivery like those tolerable by plain data transfer applications. Multimedia requires that data packets arrive on time and in the proper order at the client side. Real-time protocols and quality of service guarantees addresses this issue. Furthermore, multimedia requires transmitting large amount of traffic over the network and thus uses far more of the network’s bandwidth than in case of those basic network operations. Multicasting offers far more efficient way of transmitting such traffic over the Internet than unicasting or broadcasting ever would. The subject of this paper addresses the issue of efficient routing of such multicast traffic.